2012
DOI: 10.1073/pnas.1206868109
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting muscle diacylglycerol and triacylglycerol content by blocking fatty acid oxidation does not impede insulin sensitivity

Abstract: A low fat oxidative capacity has been linked to muscle diacylglycerol (DAG) accumulation and insulin resistance. Alternatively, a low fat oxidation rate may stimulate glucose oxidation, thereby enhancing glucose disposal. Here, we investigated whether an ethyl-2-[6-(4-chlorophenoxy)hexyl]-oxirane-2-carboxylate (etomoxir)-induced inhibition of fat oxidation leads to muscle fat storage and insulin resistance. An intervention in healthy male subjects was combined with studies in human primary myotubes. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 38 publications
7
65
0
Order By: Relevance
“…Using the muscleselective Cpt1b inhibitor, oxfenicine, Keung et al (23) showed decreased diacylglycerol (DAG) and ceramide levels following short-term treatment of obese mice. In contrast, Timmers et al (21) showed increased IMCL and DAG accumulation following 8 d of treatment with the nonselective global Cpt1 inhibitor, etomoxir. These studies revealed short-term benefits in Significance Many theories regarding the causes of insulin resistance in skeletal muscle center on the ability of muscle to oxidize fat, with evidence supporting either decreased or increased fatty acid oxidation (FAO) as causal to insulin resistance.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Using the muscleselective Cpt1b inhibitor, oxfenicine, Keung et al (23) showed decreased diacylglycerol (DAG) and ceramide levels following short-term treatment of obese mice. In contrast, Timmers et al (21) showed increased IMCL and DAG accumulation following 8 d of treatment with the nonselective global Cpt1 inhibitor, etomoxir. These studies revealed short-term benefits in Significance Many theories regarding the causes of insulin resistance in skeletal muscle center on the ability of muscle to oxidize fat, with evidence supporting either decreased or increased fatty acid oxidation (FAO) as causal to insulin resistance.…”
mentioning
confidence: 94%
“…There have been a handful of studies that have used pharmacological inhibition of Cpt1 to target insulin resistance. The results are inconsistent and, in some cases, completely contradictory due to species/model differences and methods of assessing insulin sensitivity (17)(18)(19)(20)(21)(22)(23). These studies also lack tissue specificity and are generally of short duration and/or initiated after development of insulin resistance/diabetes.…”
mentioning
confidence: 99%
“…If humans, animals or in vitro preparations of muscle are exposed to an increased availability of FAs in the presence of glucose, the oxidation of FAs increases and the oxidation and uptake of glucose decrease (Boden et al 1994, Vaag et al 1994. On the other hand, reduction of the availability of FAs by inhibiting lipolysis (Vaag et al 1991, Lim et al 2011 and blocking FA entry into the mitochondria reduces FA oxidation and increases glucose uptake and oxidation (Oakes et al 1997, Timmers et al 2012, Keung et al 2013, although there are some reports that prolonged inhibition of FA oxidation can lead to reduced glucose uptake (Dobbins et al 2001). Although the initial observations of Randle and colleagues on the reciprocal relationship between glucose and FA metabolism were made 50 years ago, the idea that increasing or reducing FA availability will reciprocally affect glucose utilisation is no less valid today.…”
Section: Substrate Competition and Reduced Insulin Actionmentioning
confidence: 99%
“…shRNA-hBRCA1-or scrambled-shRNA-treated human myotubes were incubated in 30 M BSA-conjugated palmitate/oleate mixture in DMEM for 4 h as previously described ( 34 ). Myotubes were then stained with BODIPY (Molecular Probes, Carlsbad CA) as previously described ( 35 ).…”
Section: Human Myotube Palmitate/oleate Incubation and Bodipy Imagingmentioning
confidence: 99%
“…Myotubes were then stained with BODIPY (Molecular Probes, Carlsbad CA) as previously described ( 35 ). Myotubes were imaged with a Zeiss Axiovision 4 (Zeiss, Oberkochen, Germany) as previously described ( 34,36 ).…”
Section: Human Myotube Palmitate/oleate Incubation and Bodipy Imagingmentioning
confidence: 99%